Recent bio-emerging strategies for paddy straw degradation under sustainable agriculture development - Singh, Smriti; Kumawat, Kailash Chand (Indian Farming, 2023)
The world is mired with increasing agricultural waste and resulting pollution due to its inadequate management. Paddy straws, which contribute heavily to the country's total agricultural waste, are alternatively a source of energy and important nutrients when appropriately disposed. The recent advances towards the same have been mostly in the direction of generation of renewableenergy; however, another eco-friendly approach is the in situ or on-field decomposition of these residues, which are rich in lignocellulose. This is possible via biodegradation of these components using consortia of beneficial microorganisms. This article discusses the advantages, mechanisms and microorganisms that can be and are being used for similar purposes.